Perlindungan Hukum Bagi Guru Dalam Menjalankan Tugas Profesionalnya Terkait Dengan Penerapan Punishment Untuk Mendisiplinkan Siswa - Pratama, Praditya Arcy; Budoyo, Sapto; Maretasari, Della Ayu (PGRI Kota Semarang, 2025)
Disciplinary actions carried out by teachers, which in the past were considered mediocre, have now shifted and are considered to violate human rights. On the one hand, teachers must enforce school discipline and discipline. On the other hand, they are worried aboutcriminalization by parents or child defense NGOs for allegations of violence against children. Thepurpose of this research is to find out the implementation of legal protection for teachers in providing punishment to discipline their teachers and toformulate the concept of legal protection for teachers. The method used is normative legal research. Based on the results of the research, Law Number 14 of 2005 concerning teachers and lecturers has expressly protected the profession of teachers and lecturers, but inits implementation the power of the law is still not seen to contribute to the fate of teachers as educators. The actions taken by teachers to discipline students within certain limits are seen as having a good purpose.